Analysis of Recharge Potention in Upper Cisadane Watershed - Radius Pranoto; Satyanto Krido Saptomo; Roh Santoso Budi Waspodo (Jurnal Teknik Sipil dan Lingkungan, 2016)
ABSTRACT                Human disturbance such as land use changes, urbanization, and deforestation degrade Upper Cisadane Watershed. It also causes degradation of recharge area, decrease infiltration and increase runoff. The aims of this research were to (1) identify the criticality of recharge area; and (2) analyze the potential of water recharge in Upper Cisadane Watershed. The criticality of recharge area had been identified  refers to regulation of the Minister of Forestry, Republic of Indonesia Number: P.32/MENHUT-II/2009 by scoring and overlaying of slope, soil type, rainfall, and land use map. The amount of water recharge potential was predicted by the equation issued by IWACO and WASECO (1990).             The result showed that distribution of criticality of recharge area in Upper Cisadane Watershed in 2006, 2009, and 2013 were: (1) good: 24.7%, 24.7%, 23.6%; normal: 6.9%, 6.2%, 3.7%; (3) ranging critical: 17.9%, 17.8%, 19.4%, (4) rather critical: 25.0%, 24.9%, 30.7%; (5) critical: 23.9%, 24.5%, 22.0%; and (6) very critical:  1.9%, 2.0%, 0.7% respectively. The magnitude of the potential of water recharge on average in the recharge area was in good condition; 154.5 x 106 m3, normal; 33.9 x 106 m3, ranging critical; 94.6 x 106 m3, rather critical; 130.9 x 106 m3, critical; 98.2 x 106 m3, very critical; 6.2 x 106 m3. Upper Cisadane Watershed has a potential of annual water recharge was 511.7 x 106  to 569.2 x 106 m3/year or around 14% - 15.6%   of total rainfall, with an average change in the potential of water recharge from the simulation based on the condition of recharge area in 2006-2009 decreased -0.04%, in 2009-2013 decreased -3.2% and in 2006-2013 decreased -3.3%.Keywords: recharge area, infiltration, runoff, criticality.